To analyze the expression \( \frac{1}{2}(9 - 7^0) + (-29^0) \), we first simplify the components:
-
Evaluate \( 7^0 \): By the property of exponents, any non-zero number raised to the power of zero is 1. Thus, \( 7^0 = 1 \).
-
Now substitute this back into the expression: \[ \frac{1}{2}(9 - 1) + (-29^0) \]
-
Next, evaluate \( -29^0 \): Again, any non-zero number raised to the power of zero is 1, so \( -29^0 = -1 \).
-
Substituting back, we get: \[ \frac{1}{2}(9 - 1) - 1 \]
-
Now simplify inside the parentheses: \[ 9 - 1 = 8 \]
-
So now we have: \[ \frac{1}{2}(8) - 1 \]
-
Calculate \( \frac{1}{2}(8) = 4 \): \[ 4 - 1 = 3 \]
Now, let's look at the provided options and see which matches after performing similar operations:
-
Option 1: \( \frac{1}{2}(9 - 1) - 1 \) simplifies to: \[ \frac{1}{2}(8) - 1 = 4 - 1 = 3 \]
-
Option 2: \( \frac{1}{2}(2 + 1) \) simplifies to: \[ \frac{1}{2}(3) = 1.5 \]
-
Option 3: \( \frac{1}{2}(9 - 0) + 0 \) simplifies to: \[ \frac{1}{2}(9) + 0 = 4.5 \]
-
Option 4: \( \frac{1}{2}(9 - 1) + 1 \) simplifies to: \[ \frac{1}{2}(8) + 1 = 4 + 1 = 5 \]
The only option that results in 3 is Option 1: \[ \frac{1}{2}(9 - 1) - 1 \]
Thus, the equivalent expression is Option 1: \( \frac{1}{2}(9 - 1) - 1 \).